Hollow Molybdate Microspheres as Catalytic Hosts for Enhancing the Electrochemical Performance of Sulfur Cathode under High Sulfur Loading and Lean Electrolyte - Wang, Lu; Li, Guo‐Ran; Liu, Sheng; Gao, Xue‐Ping (Advanced functional materials, 2021)
Lithium–sulfur battery possesses a high energy density; however, its application is severely blocked by several bottlenecks, including the serious shuttling behavior and sluggish redox kinetics of sulfur cathode, especially under the condition of high sulfur loading and lean electrolyte. Herein, hollow molybdate (CoMoO4, NiMoO4, and MnMoO4) microspheres are introduced as catalytic hosts to address these issues. The molybdates present a high intrinsic electrocatalytic activity for the conversion of soluble lithium polysulfides, and the unique hollow spherical structure could provide abundant sites and spatial confinement for electrocatalysis and inhibiting shuttling, respectively. Meanwhile, it is demonstrated that the unique adsorption of molybdates toward polysulfides exhibits a “volcano‐type” feature with the catalytic performance following the Sabatier principle. The NiMoO4 hollow microspheres with moderate adsorption show the highest electrocatalytic activity, which is favorable for enhancing the electrochemical performance of sulfur cathode. Especially, the S/NiMoO4 composite could achieve a high areal capacity of 7.41 mAh cm−2 (906.2 mAh g−1) under high sulfur loading (8.18 mg cm−2) and low electrolyte/sulfur ratio (E/S, 4 µL mg−1). This work offers a new perspective on searching accurate rules for selecting and designing effective host materials in the lithium–sulfur battery. Molybdate hollow spheres (CoMoO4, NiMoO4, MnMoO4) are employed as the host materials for Li–S battery, among which NiMoO4 with the moderate adsorption strength shows the highest catalytic efficiency toward sulfur conversion. The resulting S/NiMoO4 composite delivers high gravimetric capacity under high sulfur loading and lean electrolyte usage.